Isothermal section of the Ni–Mn–Sb ternary system at 773K - Du Yong; Weiqin Ao; Miao Peng; fulai liu; fusheng liu; junqin li; shuhong liu; chenying shi (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The isothermal section of the Ni-Mn-Sb ternary system at 773 K was measured by means of 117 alloys, which were analyzed by using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersion spectroscopy (EDS), and electron probe microanalysis (EPMA) techniques. The existence of 7 binary compounds named NiMn, Mn2Sb, MnSb, NiSb2, NiSb, Ni5Sb2, Ni3Sb and 2 ternary compounds named Ni2MnSb and NiMnSb were confirmed at this isothermal section. The four binary compounds Ni3Sb(Cu3Ti-type structure, space group Pmmn), Ni5Sb2(Ni5Sb2-type structure, space group C2), NiSb2 (FeS2-type structure, space group Pnnm) and Mn2Sb (Cu2Sb-type structure, space group P4/nmm) in the sub-binary systems Ni-Sb and Mn-Sb were stoichiometric compounds, the homogeneity ranges of which were negligible. While the five single phase regions in the Ni-Mn binary system and the binary compounds MnSb and NiSb showed more or less homogeneity ranges formed by replacement of Mn and Sb for Ni. The Heusler compound μ (Ni2MnSb) has L21-type ordered structure with space group Fm-3m, a = 0.6017 nm. And the crystal structure for the Half-Heusler compound κ (NiMnSb) is C1b-type (F-43m) with a = 0.5961 nm. The approximate homogeneity ranges of the two ternary compounds μ and κ at 773 K were determined.